A clinical comparison of DPOAE fine structure reduction methods. (1st March 2021) - Marcrum, Steven C.; Höfle, Eva; Picou, Erin M.; Steffens, Thomas; Kummer, Peter; Kwok, Pingling
Abstract: Objective: To evaluate two real-time methods for reducing distortion product otoacoustic emission (DPOAE) fine structure in terms of DPOAE amplitude and fine structure depth. Design: A prospective, repeated-measures design was used to assess DPOAE characteristics in response to a conventional stimulation method (Conv.), as well as for methods implementing either a generic suppressor tone (Supp.) or frequency modulation of the f2 primary tone (FM). Study sample: Eighty-three young adults (58 females) between the ages of 20 and 34 years with normal hearing completed testing for this study. Results: Use of the Conv. and FM methods resulted in consistently higher DPOAE levels relative to the Supp. method, with average advantages of 6 and 5 dB, respectively. For all methods, increased fine structure depth was observed for stimulation with lower level (25−45 dB SPL) and lower frequency (1000−3000 Hz) primary tones. Finally, use of the Supp. and FM methods resulted in significantly decreased fine structure depth relative to the Conv. method. Conclusion: Through frequency modulation of the f2 primary tone, it was possible to reduce the depth of fine structure across a clinically meaningful range of stimulation levels and frequencies without concomitant reduction in DPOAE amplitude.